2000
DOI: 10.21236/ada389545
|View full text |Cite
|
Sign up to set email alerts
|

First-Term Attrition in the Navy: Causes and Proposed Solutions

Abstract: SUMMARYMore than 18% of Navy recruits leave the service within the first 6 months, and more than 37% are discharged before the end of their first term. By reducing the attrition rate, the Navy could slash costs for recruiting, training, equipment, and related expenses. For example, the General Accounting Office estimates that in fiscal year 1996, the joint services lost an investment of $39 million by recruiting and training enlistees who separated before they had completed 6 months of service. The purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…10 Previous research indicates that cigarette smoking in the military has adverse effects on personnel health, performance, physical fitness and attrition. [14][15][16] Numerous studies have concluded that there are negative relationships between smoking and success in combat training among military personnel. [17][18] Smokers tend to exercise less and perform more poorly on military physical fitness tests.…”
mentioning
confidence: 99%
“…10 Previous research indicates that cigarette smoking in the military has adverse effects on personnel health, performance, physical fitness and attrition. [14][15][16] Numerous studies have concluded that there are negative relationships between smoking and success in combat training among military personnel. [17][18] Smokers tend to exercise less and perform more poorly on military physical fitness tests.…”
mentioning
confidence: 99%
“…15 Also, most previous studies focused on smoking as a predictor of a single or few outcomes, such as excess training costs or absenteeism, or measured relatively shortterm outcomes of smoking (e.g., attrition during the first year of enlistment). [15][16][17] Little was known about the association of smoking with longer-term personnel outcomes, such as career advancement, disciplinary problems, and reenlistment decisions. Most previous studies have been descriptive, ecological, or based on aggregated data, limiting the ability to make prospective inferences about smoking as a risk factor for subsequent personnel-related outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Also, most previous studies focused on smoking as a predictor of a single or few outcomes, such as excess training costs or absenteeism, or measured relatively short-term outcomes of smoking (e.g., attrition during the first year of enlistment) (Klesges, Haddock, & Chang, et al, 2001;Larson & Kewley, 2000;Zadoo, Fengler & Catterson, 1993). Little was known about the association of smoking with longer-term personnel outcomes, such as career advancement, disciplinary problems, and reenlistment decisions.…”
Section: Nothing On This Page Is Proprietary Informationmentioning
confidence: 99%
See 2 more Smart Citations